2022
DOI: 10.1007/s00464-021-08986-x
|View full text |Cite
|
Sign up to set email alerts
|

Elective laparoscopic cholecystectomy: recurrent biliary admissions predispose to difficult cholecystectomy

Abstract: Introduction Patients undergoing elective laparoscopic cholecystectomy (ELLC) represent a heterogeneous group making it challenging to stratify risk. The aim of this paper is to identify pre-operative factors associated with adverse peri- and post-operative outcomes in patients undergoing ELLC. This knowledge will help stratify risk, guide surgical decision making and better inform the consent process. Methods All patients who underwent ELLC between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Recurrent admissions ultimately result in increased morbidity that may actually outweigh the benefit of DLC. 11 Prompt DLC 6 to 8 weeks after discharge would ensure timely intervention and may avoid the morbidity, inconvenience, and expense of readmission. This should be emphasized and may be achieved by confirming the date of surgery before discharge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recurrent admissions ultimately result in increased morbidity that may actually outweigh the benefit of DLC. 11 Prompt DLC 6 to 8 weeks after discharge would ensure timely intervention and may avoid the morbidity, inconvenience, and expense of readmission. This should be emphasized and may be achieved by confirming the date of surgery before discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Although the TG18 guidelines are generally seen as being supportive of ELC for AC, it must be recognized that most of the nonrandomized studies included in the guidelines suffer from low sample sizes and do not conduct multivariate analysis to adjust for preoperative variables, thus subjecting them to significant bias. 3,11 The randomized studies reported in TG18 also depend on small sample sizes, short follow-up times and are largely outdated. 4e7 It must be acknowledged that some of the randomized studies listed in the TG18 guidelines such as Ozkardes ¸et al and Kolla et al actually found higher rates of operation-related adverse outcomes in the ELC group, a finding replicated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This avoids the risk of both recurrent cholecystitis and the potential problems of new stones forming in the gallbladder remnant. This also avoids a completion cholecystectomy at a later stage which may be indicated but would likely be even more challenging due to further episodes of inflammation and additional adhesions [17,18]. Fundus-first dissection offers an alternative retrograde dissection technique.…”
Section: Discussionmentioning
confidence: 99%